An in Vitro investigation of the effects of Rimonabant (a cannabinoid CB1 receptor antagonist) on cell adhesion and inflammatory associated cytokine production - Cromarty, Allan Duncan (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.